A Learning Model for Explanation Text Literacy Using Flipbook Applications in SMP/MTS - Jaya, Andri Yono Septian; Gloriani, Yusida; Khaerudin, Robia (International Journal of Educational Research Excellence (IJERE), 2024)
This research aims to develop an explanatory text literacy learning model using the flipbook application as media in SMP/MTS. The background to this problem 1) How is the planning for an explanatory text literacy learning model using the flipbook application as a medium in class VIII SMP/MTS? 2) How to implement an explanatory text literacy learning model using the flipbook application as a medium in class VIII SMP/MTS? 3) What is the effectiveness of the explanatory text literacy learning model using the flipbook application as a medium in class VIII SMP/MTS? This research uses the Research and Development (R&D) research and development method with the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model. The steps of this research consist of, needs analysis, learning model design, learning model development, implementation of learning model products, evaluation of learning model products. Data collection in this research was by collecting data from the results of expert validation questionnaires and questionnaires from student assessments. The data obtained was analyzed descriptively using a Likert scale. The results of the validation test by media experts obtained a score of 77.94%, the validation test by language experts obtained a score of 81.25%, the Indonesian language teacher's response score obtained a score of 97.33%, and the average student response obtained a score of 82.13%. The conclusion of this research is that the explanatory text literacy learning model using the flipbook application media in SMP/MTS meets the appropriate criteria to be used as a learning model by students or teachers in Indonesian language subjects with explanatory text material in class VIII SMP/ MTS students.